[tex] 12x - 36 - 6x \ is \ simplified \ to \ 6(x-6)[/tex]
The commutative property of addition states that:
[tex]a+b=b+a[/tex]
So applying this property to our expression we have:
[tex]12x - 36 - 6x=-6x+12x-36 \\ \\ \\ So \ here: \\ \\ a=12x-36 \\ \\ b=-6x \\ \\ \\ Combining \ like \ terms: \\ \\ 12x - 36 - 6x=6x-36 \\ \\ \\ Common \ factor \ 6: \\ \\ 12x - 36 - 6x=6(x-6) \\ \\ \\ Finally: \\ \\ 12x - 36 - 6x \ is \ simplified \ to \ 6(x-6)[/tex]
Evaluating expression: https://brainly.com/question/14423698#
#LearnWithBrainly